Laparoscopic excision of a solitary fibrous tumor originating from the abdominal wall: a case report. Issue 3 (15th March 2021) - Imaoka, Kouki; Nishihara, Masahiro; Yamaguchi, Megumi; Kawasaki, Yukari; Sugino, Keizo
ABSTRACT: Solitary fibrous tumors (SFTs) are mesenchymal fibroblastic tumors, and forms of SFTs that originate from the abdominal wall are extremely rare. Here we report a case of a nonpalpable SFT along the abdominal wall. Abdominal magnetic resonance (MR) imaging showed a well-circumscribed mass measuring 5 cm in diameter with heterogeneous signal intensity on T2-weighted MR images; this mass was diagnosed as a benign abdominal tumor of unknown origin. Successful laparoscopic excision of the tumor was performed. Histological examination revealed a benign extrapleural SFT. No tumor recurrence was observed after 20-month follow-up. This is the first case of laparoscopic excision of an SFT originating from the abdominal wall. Our report highlights the safety and usefulness of laparoscopic excision of abdominal wall tumors such as SFTs. This approach is an underutilized surgical treatment that can be applied to select cases of SFT in the abdominal cavity.